UTILIZING NARROW YARDS AS A FAMILY FOOD SOURCE: A CASE STUDY IN SUNGGAL DISTRICT - Fahri Alamsyah; Aadil Hussain Mir (CV. Radja Publika, 2024)
Utilizing small yards is one way to support family food security, particularly in areas with limited land. This study aims to analyze the level of utilization of small yards as a source of family food and the factors influencing it in Sunggal District. The research method used is a quantitative descriptive approach with data collection techniques through observation, interviews, and questionnaires with respondents who have small yards. The data obtained were analyzed using descriptive analysis with the help of percentages. The results show that the utilization of small yards in Sunggal District is still classified as moderate and not optimal. Most respondents have used their yards to grow food crops such as vegetables and medicinal plants, but their utilization is still simple and limited. The utilization of yards contributes to reducing household expenses and improving the quality of family food consumption. Factors influencing yard utilization include land area, level of knowledge and skills, availability of production facilities, community motivation, and government support. Based on the research results, efforts are needed to increase community capacity through counseling, training, and support for production facilities so that the utilization of small yards can be more optimal in supporting family food security.